1997
DOI: 10.1507/endocrj.44.527
|View full text |Cite
|
Sign up to set email alerts
|

Stronger Suppression of Serum Testosterone and FSH Levels by a Synthetic Estrogen than by Castration or an LH-RH Agonist.

Abstract: Abstract. Serum levels of LH, FSH and testosterone (T) were measured by radioimmunoassays in 36 patients with advanced prostate cancer before and during androgen ablation therapies. Both leuprolide acetate (LH-RH agonist: LHRH-A) and diethylstilbestrol diphosphate (DES-DP) administration decreased serum LH significantly to an undetectable level (LHRH-A: P<0.01, DES-DP: P<0.05). LHRH-A and DES-DP diminished serum FSH to 20% of the pre-treatment level (P<0.005) and to an undetectable level (P<0.001), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Previous studies have suggested several possibilities that may account for its antitumor effect. Suppression of the hypothalamic-testicular axis, thus reducing serum testosterone to castrate levels (1), and suppression of adrenal androgens such as dehydroandrostendione and dehydroepiandrosterone sulfate (14) are possible mechanism of action. In addition to these hormonally mediated effects, DES may interfere with the cell cycle and induce apoptosis of androgen-dependent and -independent prostate cancer cell lines (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested several possibilities that may account for its antitumor effect. Suppression of the hypothalamic-testicular axis, thus reducing serum testosterone to castrate levels (1), and suppression of adrenal androgens such as dehydroandrostendione and dehydroepiandrosterone sulfate (14) are possible mechanism of action. In addition to these hormonally mediated effects, DES may interfere with the cell cycle and induce apoptosis of androgen-dependent and -independent prostate cancer cell lines (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, the number of medicines approved for the treatment of CRPC has increased dramatically, and includes the hormonal agents abiraterone (14) and MDV3100 (enzalutamide), the cytotoxic agent cabazitaxel (28), an adoptive cellular immunotherapy Sipuleucel-T (29) and alpharadine, a bone-targeted radionuclide Radium-223 (30). In addition, promising early clinical data in CRPC have been obtained with cabozantinib, a tyrosine kinase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect is significantly stronger than that of surgical castration or of the administration of an LH-RH agonist [7]. We presume a potent suppressive effect on serum T might be one of the mechanisms of DES-DP action in patients with hormone-refractory prostate cancers.…”
Section: Approximatelymentioning
confidence: 79%
“…Serum levels of steroids before and during diethylstilbestrol diphosphate treatment in patients with hormone-refractory prostate cancer level, although serum levels of T are suppressed more strongly by DES-DP than by an LH-RH agonist or by bilateral orchiectomy or by combined androgen blockade with an LH-RH agonist and an androgen receptor blocker [7]. The detectable T in serum of the patients treated by an LH-RH agonist, with or without one of the anti-androgens, or surgical castration must originate from serum adrenal androgens.…”
Section: Discussionmentioning
confidence: 93%